Défendre la culture gaie. Entretien avec David Halperin - David M. Halperin; Mathieu Trachman (Genre, Sexualité et Société)
In this interview David Halperin discusses his background as an academic and as an activist. He describes the direction his present research is taking and the evolution of homosexual activism in the United States, the reasons for the increased depoliticization of homosexuality, and argues that queer theory has misrepresented the character of the lesbian and gay studies which preceded it. He also draws attention to the different ways in which queer theory has made it more difficult to grasp sexual identities as specific forms of existence. Gay culture, its political importance, and the difficulty of writing its history are at the heart of this study. However, as a passionate defender of the social constructionist approach of the history of sexuality, Halperin deplores the bracketing of queer subjectivity, and in this most recent project he tackles the study of male homosexuality, not as a distinctive sexual practice, but as a specific cultural orientation, with its unique object-choices and lifestyles.